The Quaestiones III 2 and 3 of Alexander of Aphrodisias and the problem of the sensitive alteration - Zingano, Marco (Estudios de Filosofía, 2009)
as Alexander examines Aristotle’s De anima II 5, he is confronted with the problem of explaining what sort of alteration sensation is. His answer was very in uential, especially after Quaestio III 3 had been translated into Latin by Gerard of Cremona, based on an Arabic version of it. In fact, it is still very in uential, for it is generally considered by modern commentators of the De anima. But a close scrutiny of De anima II 5 can raise doubts about some theories Alexander ascribed to Aristotle concerning the relationship between being affected or altered and sense-perception. In his paper Zingano intends to show how Alexander’s reading of Aristotle’s De anima II 5 contains a crucial element for the thesis according to which ‘being affected’ has little or no relevancy in the explanation of perception as a discriminating faculty.